Intermediate Coupling Regime in Dilatonic f(R,T) Inflationary Universe - Francisco A. Brito; Carlos H. A. B. Borges; Jose A. V. Campos; Francisco G. Costa (Universe)
In the present work, we study cosmology in dilatonic <semantics>f(R,T)</semantics> gravity to address the inflationary phase of the early universe. As usual, in dilatonic gravity, the scalar potential assumes the exponential form. However, this potential is not good enough to be in accordance with the Planck 2018 data. More strikingly, the generalized <semantics>β</semantics>-exponential cannot take this into account either. It is just only presence of the dilatonic sector, in the intermediate coupling regime, that can help the theory to be in full accordance with the observational data.